Guiding principles for change in undergraduate education: An analysis of a departmental team’s change effort - Courtney Ngai; Mary E. Pilgrim; Daniel L. Reinholz; Karen Falkenberg; Chris Geanious; Joel C. Corbo; Sarah B. Wise; Clara E. Smith; Amelia Stone-Johnstone (Physical Review Physics Education Research, 2023)
The practices of a departmental action team (DAT) are examined to characterize their change effort in their undergraduate program. The DAT’s effort was guided by the DAT model’s six core principles. The core principles are grounded in best practices for higher education and organizational change literature. Meeting minutes, facilitator journal entries, and exit interviews are analyzed to identify ways in which the core principles influenced the change effort. This analysis provides insight into how the core principles can be leveraged to enact positive change in education. Furthermore, this work provides a method for researchers to characterize other complex change efforts.